Using Kahoot! to Increase Students’ Motivation in Post-Pandemic Hybrid Learning - Haerul Pathoni; Alrizal Alrizal; Muhammad Akbar Pisnaji; Louisiana Muliawati (Postgraduate, University of Mataram, 2023)
The lack of students’ motivation is one of the issues in implementing hybrid learning after the pandemic. This study aims to determine the effectiveness of using Kahoot! to increase the motivation of students studying on Hybrid learning after the pandemic. The type of research is a pre-experimental study in the form of one-group pretest-posttest design. This research was conducted at SMA Negeri 3 Kota Jambi from February to March 2022. The subjects of this study were grade 10th students who were determined by cluster random sampling technique. Research data were collected through questionnaires that were distributed to students. Based on the results of the paired t-test which gets the result of the sig value of 0.000 which is smaller than 0.05. Based on the N gain test, the result obtained is 0.36 which is in the medium category. It can be conclude that there is a significant increase in students’ learning motivation after using Kahoot! in the hybrid learning